Blood lactate and ventilatory response in aerobically trained athletes with different exercise protocols: A comparison of two methods - Gailiuniene, A.; Popinigis J.; Suchanowski, A. (Education. Physical training. Sport, 1998)
Blood lactate and ventilatory response in aerobically trained athletes with different exercise protocols: a comparison of two methods. The purpose of this study was to determine the effects of continuous increased work intensity (IWI) for determination of ventilation (VE), ventilatory equivalent for oxygen (VE/VO2) heart rate (HR), oxygen uptake (VO2), mechanical power (W) corresponding to the cappillary blood lactate (La) of 4 mmol×L-1 and VO2max values in all-round aerobically trained athletes (controls) and specifically trained triathletes. All-round aerobically trained control subjects - oarsmen, swimmers, soccer players - (n=8) and specifically trained triathletes (n=5) (18-22 years) performed continuously increasing cycle ergometer exercise tests of 2 kinds: 1) The step-ladder protocol was preceded by a 2 min warm-up at 50W and started at a workload 50W with increases of 50 W×2 min-1 to their maximum tolerance and VO2max (IWI1) and 2) ergometric test, when work rate (2 W×kg-1) was adjusted to the ventilatory threshold and then increased in work rate step (20 W×min-1) to maximum work capacity (IWI2). Was determing the ventilatory treshold (VT) respiratory compensation treshold (RCT) and lactate treshold (LaT). Significantly higher VO2max and lower HR values (p<0.05) were noted at the IWI2 than IWI1 condition and in the triathletes than controls all-round aerobically trained athletes. Comparison Vemax values from the IWI1 and IWI2 tests showed a significantly lower mean values at IWI2 than IWI1 and in triathletes than controls all-round trained athletes (p<0.05). Different max blood lactate values between the two conditions were noted at 3 min post test (p>0.05) and in controls were higher than in triathletes. The characteristics ofmetabolic and performance variables in the different modalities of tests IWI1 and IWI2 at VT, RCT and LaT are different significant differences were found between the results obtained using different protocols and different criteria to examine absolute and relative values of anaerobical threshold.